A comprehensive performance evaluation of food and beverages industry in Malaysia using GRA Models / Farah Azaliney Mohd Amin ... [et al.] - Mohd Amin, Farah Azaliney; Abd Razak, Aina Nashita; Abdul Malek, Nurul Alisya; Shahrudin, Nurul Azzwin Azzura (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The current population of Malaysia is 33,481,580 has significantly influenced the demand of its local food and beverage (Department of Statistics Malaysia, 2023). Recently, the F&B industry has generated RM220.33 billion in revenue and is anticipated to expand by 7.95% yearly until 2027 (Statista, 2023). Therefore, the F&B industry is one of the key sectors that contribute to the rise of the nation's economy comprising Gross Domestic Product (GDP), revenue, employment and foreign exchange earnings (Hoe et al., 2020). This situation has indirectly increased competition between companies especially in the F&B sector. Thus, the company is searching for a comprehensive performance evaluation method that is not only easy to apply but can also accurately analyze the overall company's performance as a whole. Performance evaluation is critical in today's environment since companies must defend their market position against their competitors (Zandi et al., 2014). An effective evaluation methodology can benefit the company itself in maximizing their resources and implementing more appropriate business strategies. The evaluation system can also assist companies in the same industry for benchmarking as an effort to improve performance periodically which finally leads to long-term success (Nguyen et al., 2020).